Game of Stones: feasibility randomised controlled trial of how to engage men with obesity in text message and incentive interventions for weight loss. Issue 2 (25th February 2020) - Dombrowski, Stephan U; McDonald, Matthew; van der Pol, Marjon; Grindle, Mark; Avenell, Alison; Carroll, Paula; Calveley, Eileen; Elders, Andrew; Glennie, Nicola; Gray, Cindy M; Harris, Fiona M; Hapca, Adrian; et al.
Abstract : Objectives: To examine the acceptability and feasibility of narrative text messages with or without financial incentives to support weight loss for men. Design: Individually randomised three-arm feasibility trial with 12 months' follow-up. Setting: Two sites in Scotland with high levels of disadvantage according to Scottish Index for Multiple Deprivation (SIMD). Participants: Men with obesity (n=105) recruited through community outreach and general practitioner registers. Interventions: Participants randomised to: (A) narrative text messages plus financial incentive for 12 months (short message service (SMS)+I), (B) narrative text messages for 12 months (SMS only), or (C) waiting list control. Outcomes: Acceptability and feasibility of recruitment, retention, intervention components and trial procedures assessed by analysing quantitative and qualitative data at 3, 6 and 12 months. Results: 105 men were recruited, 60% from more disadvantaged areas (SIMD quintiles 1 or 2). Retention at 12 months was 74%. Fewer SMS+I participants (64%) completed 12-month assessments compared with SMS only (79%) and control (83%). Narrative texts were acceptable to many men, but some reported negative reactions. No evidence emerged that level of disadvantage was related to acceptability of narrative texts. Eleven SMS+I participants (31%) successfully met or partially met weight loss targets. The cost of the incentive per participant was £81.94 (95% CI £34.59 to £129.30). Incentives were acceptable, but improving health was reported as the key motivator for weight loss. All groups lost weight (SMS+I: −2.51 kg (SD=4.94); SMS only: −1.29 kg (SD=5.03); control: −0.86 kg (SD=5.64) at 12 months). Conclusions: This three-arm weight management feasibility trial recruited and retained men from across the socioeconomic spectrum, with the majority from areas of disadvantage, was broadly acceptable to most participants and feasible to deliver. Trial registration number: NCT03040518 .